Ordinance no. 11-An Ordinance Concerning Offenses and Disorderly Conduct, § 34, Ilwaco Town Council (1891) (Washington). - (:unkn) unknown (My University, 1891)
If any person or persons shall use or caused to be used or encouraged the use of any bean-shooter. air-gun, cross-bow or other contrivance or invention used in shooting or throwing beans, stones pebbles, bullets, shot or other substance or thing in or upon any street, park, lane, alley or other public place in the Town shall be guilty of a misdemeanor and upon conviction thereof before the Police Court shall be fined not less than Two nor more than Forty $Dollars...
Keywords: DISCHARGE